Синтез, фізико-хімічні властивості та дослідження гострої токсичності похідних 1,2,4-тріазолу, що містять ядро тіофену - Саліонов, Володимир Олександрович; Салионов, В. А.; Salionov, V. A. (Запорізький державний медичний університет, 2015)
Сучасні лікарські засоби повинні мати певні характеристики, серед них – мала токсичність і висока ефективність. З цією метою вважали за доцільне синтезувати ряд естерів 2-(4-R-5-(тіофен-2-іл)-4H-1,2,4-тріазол-3-ілтіо)ацетатних кислот, дослідити їхні фізико-хімічні властивості, а також вивчити гостру токсичність сполук, що одержали, для виявлення характеру та вираженості їхньої ушкоджуваної дії на організм експериментальних тварин. Етерифікацією відповідних 2-((4-R-5-(тіофен-2-іл)-4H-1,2,4-тріазол-3-іл)тіо)ацетатних кислот метиловим, етиловим, ізопропіловим і бутиловим спиртами за наявності каталітичної кількості концентрованої сульфатної кислоти отримали 16 нових сполук. У всіх випадках встановлені фізико-хімічні константи, а будова підтверджена комплексним використанням елементного аналізу, ПМР- та ІЧ- спектроскопії. Для всіх сполук дослідили та встановили показники гострої токсичності. При дослідженні гострої токсичності естерів відповідних 2-((4-R-5-(тіофен-2-іл)-4H-1,2,4-тріазол-3-іл)тіо)ацетатних кислот встановили, що всі сполуки, котрі досліджували, належать до 4 або 5 класів токсичності та є малотоксичними і практично нетоксичними, а їх ЛД50 знаходиться в межах від 525±51 мг/кг до 2250±200 мг/кг . Современные лекарственные средства должны иметь определённые характеристики, среди которых – малая токсичность и высокая эффективность. С этой целью мы считали целесообразным синтезировать ряд эфиров 2-(4-R-5-(тиофен-2-ил) -4H-1,2,4-триазол-3-илтио)ацетатных кислот, исследовать их физико-химические свойства, а также изучить острую токсичность полученных соединений для выявления характера и выраженности их повреждающего действия на организм экспериментальных животных. Этерификацией соответствующих 2- ((4-R-5-(тиофен-2-ил)-4H-1,2,4-триазол-3-ил)тио)ацетатных кислот метиловым, этиловым, изопропиловым и бутиловым спиртами при наличии каталитического количества концентрированной серной кислоты получено 16 новых соединений. Во всех случаях установлены физико-химические константы, а строение подтверждено комплексным использованием элементного анализа, ПМР- и ИК-спектроскопии. Для всех соединений исследованы и установлены показатели острой токсичности. При исследовании острой токсичности эфиров соответствующих 2-((4-R-5-(тиофен-2-ил)-4H-1,2,4-триазол-3-ил)тио)ацетатных кислот установлено, что все исследуемые соединения относятся к 4 или 5 классам токсичности, являются малотоксичными и практически нетоксичными, а их ЛД50 находится в пределах от 525±51 мг/кг до 2250±200 мг/кг . The aim of research. Modern drugs must have certain characteristics, such as low toxicity and high efﬁciency. Special attention should be given to esthers of 2-(1,2,4-triazoles-3-iltio)acetic acids. It has been found that compounds of this class are able to show analgesic, neuroleptic, diuretic, anti-inﬂammatory, mild antimicrobial and other biological activities and also can be intermediates for the synthesis of amides, hydrazides, ilidenhidrazides and bicyclic structures.Therefore, we synthesized a series of esthers of 2-(4-R-5- (thiophene-2-yl)-4H-1,2,4-triazoles-3-iltio)acetic acids, to explore their physical and chemical properties, to explore the acute toxicity of the obtained compounds, to identify the nature and severity of their damaging effects on the body of experimental animals.Materials and methods. Esthers of 2-((4-R-5-(thiophene-2-yl)-4H-1,2,4-triazol-3-yl)thio)acetic acids have been obtained by the etheriﬁcation of the corresponding 2-((4-R-5-(thiophene-2-yl)-4H-1,2,4-triazol-3-yl)thio)acetic acids with methyl, ethyl, isopropyl and butyl alcohols in the presence of the catalytic amount of concentrated sulfuric acid.The tabular rapid method of V. B. Prozorovskiy which was used in a number of scientists practical research, has been selected for the acute toxicity study. Test compounds were introduced intraperitoneally in doses from the logarithmic scale. Results. 16 new derivatives of 2-((4-R-5-(thiophene-2-yl)-4H-1,2,4-triazoles-3-yl)thio)acetic acids have been synthesized. Physicalchemical constants have been checked for all synthesized compounds and their structure has been conﬁrmed by using elemental analysis, 1H NMR- and IR-spectroscopy. The indicators of acute toxicity have been studied for all synthesized compounds. The acute toxicity study of the esters of 2-((4-R-5-(thiophene-2-yl)-4H-1,2,4-triazoles-3-yl)thio)acetic acid shows that all compounds belong to the 4th or 5th grade of toxicity, they are practically non-toxic and low-toxic and their LD50 is in the range of 525±51 mg/kg to 2250±200 mg/kg.
Синтез, физико-химические свойства и исследование острой токсичности производных 1,2,4-триазола, которые содержат ядро тиофена
Synthesis, physical-chemical properties and research of acute toxicity of 1,2,4-triazole derivatives containing thiophene core
Keywords: 1,2,4-тріазол; тіофен; естери; токсичність високого ступеня; 1,2,4-триазол; тиофен; эфиры; токсичность высокой степени; 1,2,4-triazole; Thiophene; Esthers; Acute Toxicity Tests